Betriebliche Bündnisse für Beschäftigung in der Krise 2008/2009 erfolgreich - Lutz Bellmann; Hans-Dieter Gerner (Wirtschaftsdienst, 2012)
Die Entwicklung der Arbeitslosigkeit und Beschäftigung verlief in Deutschland 2008/2009 günstiger als nach anderen Krisen. Betriebliche Bündnisse für Beschäftigung spielten dabei eine besondere Rolle. Frühere Studien hatten unklare Beschäftigungseffekte konstatiert. Die Autoren kommen auf Basis einer Auswertung von Daten des Betriebspanels des Instituts für Arbeitsmarkt- und Berufsforschung zu einem positiven Ergebnis. – – The favourable employment records of the German economy during the crisis 2008/2009 is related to the pacts for employment and competitiveness concluded at the company level and characterized by concessions from both bargaining partners. In these pacts work councils agree to company-specific deviations from an industry-level contract such as reduced wages in exchange for employment guarantees. In our analysis we use the IAB-Establishment Panel Survey data from the years 2006 to 2010. We find evidence suggesting that companies which adopted these pacts during the crisis reduced the number of employees less since they were more active with respect to specific measures to cope with the crisis.
Keywords: J21; J31; J52; 330